2017
DOI: 10.18632/oncotarget.17106
|View full text |Cite
|
Sign up to set email alerts
|

In silico gene expression analysis reveals glycolysis and acetate anaplerosis in IDH1 wild-type glioma and lactate and glutamate anaplerosis in IDH1-mutated glioma

Abstract: Hotspot mutations in isocitrate dehydrogenase 1 (IDH1) initiate low-grade glioma and secondary glioblastoma and induce a neomorphic activity that converts α-ketoglutarate (α-KG) to the oncometabolite D-2-hydroxyglutarate (D-2-HG). It causes metabolic rewiring that is not fully understood. We investigated the effects of IDH1 mutations (IDH1MUT) on expression of genes that encode for metabolic enzymes by data mining The Cancer Genome Atlas. We analyzed 112 IDH1 wild-type (IDH1WT) versus 399 IDH1MUT low-grade gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 65 publications
7
87
0
Order By: Relevance
“…We and others showed that IDH1 MUT cells are more dependent on mitochondrial oxphos, as compared to IDH1 WT cells (4,27). In addition, we reported that cells of the patient-derived IDH1 MUT oligodendroglioma xenograft model E478 are packed with mitochondria, suggesting that IDH1 MUT gliomas revert to mitochondrial metabolism (28).…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…We and others showed that IDH1 MUT cells are more dependent on mitochondrial oxphos, as compared to IDH1 WT cells (4,27). In addition, we reported that cells of the patient-derived IDH1 MUT oligodendroglioma xenograft model E478 are packed with mitochondria, suggesting that IDH1 MUT gliomas revert to mitochondrial metabolism (28).…”
mentioning
confidence: 65%
“…We previously determined that IDH1 MUT HCT116 cells are more dependent on oxphos than are IDH1 WT HCT116 cells (4). Because cisplatin, but not carboplatin, strongly impairs oxphos and mitochondrial function (37), we investigated whether, besides the reduced NADPH production capacity, the increased sensitivity of IDH1 MUT cells to cisplatin is caused by this metabolic phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IDH1 MUT induces metabolic rewiring that is not fully understood [14,15] but exploration of differences in expression levels of metabolic enzymes is a promising investigational approach. The effects of IDH1 MUT on the expression of genes that encode for metabolic enzymes offer an opportunity to demonstrate the possibilities of the cBioPortal to perform data integration, exploration and analysis.…”
Section: Resultsmentioning
confidence: 99%